Is Stock Market Crash Predictable? The Case Study of Stock Markets in Malaysia, Indonesia, Korea and Singapore - Ng, Ho Keng (2008)
What is the stock market? A stock market is a market place that enables trading of company stocks, other forms of securities (such as bonds, debentures, and equity securities) and derivatives (for example, futures, forwards, options, and swaps). Stock market is an important source for companies or fund raisers to raise money and for investors or traders to make or loose money. It is also a market place for speculators to make arbitraged investment for financial gain. Due to its complexity and economic implications, it involves all market participants from central bank being the policy regulators, to financial institutions, investors, large corporation and many others. The stock market performance is a direct reflection of a country’s economy development and financial performance. Should the financial crisis arises, it affects not only the corporations, individual investors or households, but also the entire economy on a large scale, the implication of the country is profound from the economical, political and social perspectives. Today, the size of world stock market capitalization is estimated to be at about $600 trillion.